FAKTOR EKSTERNAL DAN INTERNAL YANG MEMENGARUHI MOTIVASI DALAM MEMENUHI KEWAJIBAN PERPAJAKAN - Budiarti, Komang Mega; Yaniartha, Putu Dyan (E-Jurnal Akuntansi, 2015)
The level of compliance is based on how much motivation taxpayers in meeting tax obligations, sourced from external and internal factors. The purpose of this study was to determine the effect of each variable perceptions of corruption, gender, and moral norms on motivation in meeting tax obligations. The location of this study in the Tax Office Primary South Badung. Convenience sampling technique and the sample was 99 respondents using individual taxpayer non-employees. The collection of data by the media questionnaires and analysis techniques used multiple linear regression with dummy variables. The results showed that each of these variables negatively affect the perception of corruption cases, the gender effect, and moral norms have positive influence on the motivation in meeting tax obligations.
Keywords: perceptions of corruption, gender, moral norms